Examination of Preschool Teachers' Opinion on Alternative Assessment - Kaya, İsa (Horizon Research Publishing, 2018)
This research intended to determine the alternative assessment methods used by the preschool teachers and their opinions, knowledge and competencies related to these methods. The research group of the study comprised of 10 kindergarten teachers working in Konya province during the 2017-2018 academic year in Turkey. The data obtained through the semi-structured interview form were evaluated by descriptive analysis. As a result of the research, it has been understood that preschool teachers have benefited from play-based assessment in order to gain concrete information in recognizing and evaluating the children through play. In the portfolio assessments, they have different opinions and applications in using the information and activities in the portfolio. In the program-based assessment, teachers assess children within the framework of training plans through a variety of forms, but teachers claimed that it is not effective to use the program-based approach to assess the aims and achievements of the program and the development of students. Moreover, it has been stated that the dynamic assessment approach is a new and unknown approach to the teachers, and the applications on this approach are limited. Teachers have found themselves unsatisfied in implementing alternative assessment approaches, but it has been understood that teachers are willing to develop themselves.
Keywords: Preschool Education; Alternative Assessment; Portfolio; Program Based Assessment; Play Based Assessment; Dynamic Assessment